Are mental health services getting better at responding to abuse, assault and neglect?. (7th February 2016) - Read, J.; Sampson, M.; Critchley, C.
Abstract : Objective: To determine whether staff responses to abuse disclosures had improved since the introduction of a trauma policy and training programme. Method: The files of 250 clients attending four New Zealand mental health centres were audited. Results: There was a significant improvement, compared to an audit prior to the introduction of the policy and training, in the proportion of abuse cases included in formulations, and, to a lesser extent, in treatment plans. There was no significant improvement in the proportion referred for relevant treatment, which remained at less than 25% across abuse categories. The proportion of neglect disclosures responded to was significantly lower than for abuse cases. Fifty percent of the files in which abuse/neglect was recorded noted whether the client had been asked about previous disclosure, and 22% noted whether the client thought there was any connection between the abuse/neglect and their current problems. Less than 1% of cases were reported to legal authorities. People diagnosed with a psychotic disorder were significantly less likely to be responded to appropriately. Conclusion: Future training may need to focus on responding well to neglect and people diagnosed with psychosis, on making treatment referrals, and on initiating discussions about reporting to authorities.